Do Adolescents Who Regularly Attend Religious Services Stay Out of Trouble? Results From a National Sample. (November 2016) - Salas-Wright, Christopher P.; Lombe, Margaret; Vaughn, Michael G.; Maynard, Brandy R.
The relationship between religious service attendance and adolescent externalizing behavior is well established in the aggregate, but little is known about what behavioral and psychosocial differences may or may not exist among adolescents who regularly attend religious services. Using a nationally representative sample of frequent religious service attending adolescents ( N = 26, 765), latent class analysis and multinomial regression were used to examine the relationships between latent externalizing classes and protective factors related to self-control. Results revealed a four-class solution comprised of a normative class (66.52%) as well as three externalizing classes: substance users (17.17%), fighters (12.65%), and severe offenders (3.66%). Compared with the normative class, members of the externalizing classes were significantly less likely to benefit from individual, parental, and academic protective factors related to self-control. Findings suggest that regular religious service attendance is relevant to externalizing behavior, but that it does not function as a panacea.